Artificial intelligence and financial behaviour - Viale, Riccardo; Mousavi, Shabnam; Filotto, Umberto; Alemanni, Barbara (Behavioural financial regulation and policy (befairly) series, 2023)
"Following rapid technological advancements that have taken place throughout the late 20th and early 21st centuries, this intriguing book provides a dynamic agenda for the study of artificial intelligence (AI) within finance. Through an in-depth consideration of the use of AI, it utilises case-study examples to investigate AI's effectiveness within investment and banking. Artificial Intelligence and Financial Behaviour examines to what extent AI can guide people to improve their financial wellbeing. It explores potential effects of, and problems with, specific technologies, as well as describing current regulatory considerations regarding the use of AI and machine learning. Chapters succinctly portray the impact AI may have on investor and trader behaviour. This highly informative book will be beneficial for students and researchers studying behavioural and regulatory economics. It will also be immensely useful for financial regulators who are analysing problems from contemporary points of view"--